Few, Activity-Dependent, and Ubiquitous VGLUT1/VGAT Terminals in Rat and Mouse Brain - Fattorini, Giorgia; Ciriachi, Chiara; Conti, Fiorenzo (Frontiers in Cellular Neuroscience, 2017)
In the neocortex of adult rats VGLUT1 and VGAT co-localize in axon terminals which form both symmetric and asymmetric synapses. They are expressed in the same synaptic vesicles which participate in the exo-endocytotic cycle. Virtually nothing however is known on whether VGLUT1/VGAT co-localization occurs in other brain regions. We therefore mapped the distribution of terminals co-expressing VGLUT1/VGAT in the striatum, hippocampus, thalamus, and cerebellar and cerebral cortices of rats and mice. Confocal microscopy analysis revealed that, in both rat and mouse brain, VGLUT1/VGAT+ terminals were present in all brain regions studied, and that their percentage was low and comparable in both species. These results provide the first demonstration that co-expression of VGLUT1 and VGAT is a widespread phenomenon. Since VGLUT1/VGAT+ axon terminals are regulated in an activity-dependent manner and co-release glutamate and GABA, we hypothesize that, though not numerous, they can contribute to regulating excitation/inhibition balance in physiological conditions, thereby playing a role in several neurological and psychiatric diseases.